Time-Varying Effect of Ductile Flexural Toppling Failure on Antidip Layered Rock Slope - Cai, Junchao; Zheng, Da; Ju, Nengpan; Wang, Jue; Zhou, Xin; Li, Da (Frontiers in Earth Science, 2022)
Ductile flexural toppling failure is a common form of toppling failure, and it is the product of long-term geological history and shows the characteristics of long-term deformation and progressive failure. The creep characteristics of rock mass have been seldom considered in the current research on toppling, especially interlayer creep of rock layers in the process of toppling. Based on the thought of deformation stability analysis, the flexural toppling failure was divided into the following four stages: start-up, rapid deformation, transient stability, and long-term creep stages. Combined with mechanical analysis, the developmental conditions of the start-up, transient stability, and long-term creep development stages are discussed respectively. Finally, several cases were selected to analyze the stage and the stability of the toppling deformation body, as well as to verify the rationality of the mechanical analysis condition. Study results show that the start-up conditions meet Equation 2, the rock layer inclination and slope angle is 0.5π−φ in the transient stability stage, and that angle is the infinite 0.5π in the long-term creep stage. Other external forces (such as water pressure) will intensify the development of ductile flexural toppling failure, so that the angle between the toppled bedding surface and the slope surface increases. It is of great significance to analyze the development stage of the ductile flexural toppling, comprehensively analyze and evaluate the stability of the ductile flexural toppling, reasonably develop and utilize its self-stability ability, and set up support measures.